Law Regarding the Status of Children Outside of Wedlock: in the Perspective of the Rights of Parents and Children - Ika Anisatul Fatma Fitria; Indryana Widi Ardhianty; Husaini, Wahyu Nurul; Dian Latifiani; Muhammad Adymas Hikal Fikri (Enigma in Law, 2023)
The Indonesian state, as stated in the 1945 Constitution, initially declared itself a legal state before undergoing amendments. After the amendment, the statement changed to "Indonesia is a state of law." This means that every action taken by the government or state must comply with the legal provisions in force in Indonesia. The principle of the rule of law is regulated in the 1945 Constitution, Article 1 Paragraph (3), both before and after the amendment, indicating that Indonesia is a country based on law. Indonesian law also regulates the rights and obligations of parents in the modern era. The development of modern society brings changes in interpersonal relationships, especially in the family context. The main issue that emerged was regarding the status of children born out of wedlock, reflecting shifts in social values and raising complex legal questions regarding the rights of parents and children. With the significant increase in the number of children born outside of marriage, there is a need to review the legal system that regulates the status of children outside of marriage. The primary focus is on the parents' and children's rights perspective, with attention to child recognition, custody, and financial responsibilities.